The International Vehicle Aerodynamics Conference - International Vehicle Aerodynamics Conference (2014 : Holywell Park, Loughborough, Great Britain); ScienceDirect eBooks (Cambridge, UK : Woodhead Publishing, 2014)
Aerodynamics has never been more central to the development of cars, commercial vehicles, motorbikes, trains and human powered vehicles, driven by the need for efficiency: reducing carbon dioxide emissions, reducing fuel consumption, increasing range and alleviating problems associated with traffic congestion. Reducing vehicle weight makes it more challenging to ensure that they are stable and handle well over a wide range of environmental conditions. Lighter structures are also more vulnerable to aerodynamically induced vibration. Alongside this, customers demand an environment that is quiet, comfortable and maintains their vision of the world around them in all weathers. These aims must be met by designing vehicles that engage customers emotionally, promoting the brand values of manufacturers and operators. This can only be done by collaboration between designers and aerodynamicists.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed November 20, 2014).
Elsevier
Keywords: Motor vehicles -- Aerodynamics -- Congresses; Aerodynamics -- Congresses; TECHNOLOGY & ENGINEERING -- Engineering (General); Aerodynamics; Motor vehicles -- Aerodynamics; Electronic books